Effect Of Papaya Leaf Extract (Carica Papaya L) As A Bioinsecticide To Remove Cage Flies (Stomoxys calcitrans) - Bagus Kristanto, Dery; Parida Hutapea, Henny; Ambarwati, Septiana (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
This research investigates the effectiveness of papaya leaf extract (Carica papaya L.) as a bioinsecticide against stable flies (Stomoxys calcitrans) and aims to identify the most effective concentration and solvent for killing these pests. Conducted using a Completely Randomized Design (CRD), the study utilized papaya leaf extracts obtained through maceration at concentrations of 10%, 15%, and 20%, with 96% ethanol and aquades as solvents. Phytochemical analysis confirmed the presence of beneficial compounds such as alkaloids, flavonoids, and saponins. The one-way ANOVA results revealed a significant impact of the ethanol-based extract on fly mortality, with a p-value of 0.00, while aquades showed no significant effect (p = 0.065). Notably, a 20% concentration of the ethanol extract achieved 100% mortality of stable flies within 50 minutes, indicating that papaya leaf extract is a cost-effective and environmentally friendly bioinsecticide, particularly when using ethanol as a solvent.